Development of a Drug Information Service Collaborative in Academia. Issue 3 (March 2020) - Kim, Jeeseon; Hoover, Rebecca; Perkins, Scott; Advani, Ashish
Evidence-based medicine (EBM) has been positively accepted by clinicians; however, there are barriers to practicing EBM that create gaps between EBM and current clinical practice. A pharmacist-led drug information (DI) service initiative was established to overcome common barriers to practicing EBM. The service utilizes technology and a collaborative model among otherwise independent academic DI centers to provide efficient high-quality service to health care professionals. It was piloted at a large health care system with positive user satisfaction. The unique technological collaborative has shown several benefits, including increased efficiency and peer learning among DI pharmacists.